PENGARUH PENGGUNAAN MEDIA POWER POINT TERHADAP HASIL BELAJAR SENI RUPA SISWA SMP NEGERI 27 PADANG - Siska Oktaria, Dr. Ramalis Hakin, M.Pd., Drs. Abd. Hafiz, M.Pd. (Serupa The Journal of Art Education, 2017)
The purpose of this through to understand that there is an influence of using power point media to the result of art at grade Junior High School 27 Padang. The kind of through that used is experiment interpretation score of posttest and then by technique interpretation encode for processing Random Sampling. This encode for processing collected by the test in the result of lesson. Finding in this through showing that : the result of student’s in the lesson by using power point media is better, just than with students who teached without using a conventional media. That’s mean using power point media needed to all of students for improving the result of students in the lesson specially for art in art at Junior High School 27 Padang.Keywords: Power Point media